IDENTIFIKASI BAKTERI Escherichia Coli PADA SAUS MAKANAN ATAU JAJANAN CILOK DI SEKOLAH DASAR (SD) KECAMATAN INDRALAYA SELATAN KABUPATEN OGAN ILIR - Hikmah, Al; Prasetyo, Dani; Ernia, Rima (Universitas Imelda Medan, 2023)
Food poisoning often occurs in elementary school children due to the lack of personal and environmental hygiene. According to children tend to choose unhealthy foods because regardless of the physical/chemical properties of food, taste, brand, availability and environment. The environment such as personal hygiene from food vendors is one of the factors that influence food conditions. This study aims to determine whether there is Escherichia coli bacteria on cilok sauce in Junior High Schoolab So1th Indralaya District. The results of the study by identifying Escherichia coli bacteria in cilok sauce, namely the isolation test of bacteria on LB media, obtained 8 out of 10 samples contaminated with bacteria. The EMB test results obtained 3 out of 8 samples that were positive for Escherichia coli. For bacterial tests with biochemical tests, SIM, MR, citrate, 3 positive samples of Escherichia coli bacteria were obtained where there was a color change. Citrate changes from green to blue, SIM is indicated by the formation of a pink indole ring and the MR test changes the solution to a pink color.